Modeling and analysis of CO2 emissions in million tons of sectoral greenhouse gases in Indonesia - Hafizan, Juahir; Mustafa, Mamat; Budiono, R; Sukono, .; Supian, S.; Nurzaman, M (2019)
Economic sector development is an effort to increase national economic growth which is usually measured by increasing Gross Domestic Product (GDP). But economic sector development affects CO2 emissions in million tons of sectoral greenhouse gases. Therefore, this paper performs modeling and analysis of CO2 emissions in million tons of sectoral greenhouse gases in Indonesia. Sectors analysed include: Industrial, commercial, household, transportation, power plant, and others. The objective is to obtain a model estimator and determine the level of sectoral CO2 emissions contribution to total CO2 emissions in Indonesia. Modeling is done by using Cobb-Douglas multiplicative production function approach. While to make estimation of model parameters is done by using Ordinary Least Square (OLS) method. The analysis results show that sectors: Industrial, commercial, household, transportation, power plant, significantly contribute to total CO2 emissions. While the other sectors do not significantly affect the total CO2 emissions. The analysis results also show that the five-sector CO2 emission contribution model for total CO2 emissions significantly follows Cobb-Douglas multiplicative function, with correlation strength level which is 99.9% coefficient of determination. Thus, the model estimators obtained are excellent and can be used to determine the level of sectoral CO2 emissions contribution to total CO2 emissions in Indonesia.